The value of interior audit commissions in the application of combined governance - Abdulahad, Alaa Fareed (International Journal of Psychosocial Rehabilitation, 2020)
The action of interior audit is an essential pillar of combined governance, hence the need to focus on activating the foundation of combined governance to insure the improvement and processing of-the parts of the interior audit action identified by the Institute of Interior Auditors, and that the presence of audit commissions in bond stock companies contributes to the strengthening of governance practices and mechanisms of implementation, as well as contributes to the strengthening of communication and coordination in the middle of interior and exterior parties, and from this point of view this study was based on identifying the concept of combined governance in bond stock companies and their intention. Identifying the diverse foundation for the management of companies and increasing their efficiency and credibility, and showing the role played by each of the audit commissions and interior audit sought to apply combined governance, and for the purpose of achieving these intention was conducted a survey study was conducted under which distributed (130) questionnaire sought (120) questionnaire, and the investigation er relied in the search of forms on the statistical program SPSS, and one of the most important findings of the investigation was that the existence of combined governance It is mandatory to create a "regulatory" arrangement that contributes to developing the gain of bond stock companies by determining the distribution of powers and responsibilities in the middle of the diverse parties involved in the work of the association, and it is essential for the existence of an efficient interior audit figure and an audit commission that contributes to the protection of shareholders’ rights, the preservation of funds and the provision of reliable knowledge, and there is a morally significant correlation in the middle of interior audit and audit commissions in bond stock companies and combined governance, in turn, both of which contribute to the application of combined governance.